InfoTrac college edition workbook for Crooks and Baur's our sexuality - Galupo, Paz (Thomson/Wadsworth, 2005)
This free guide contains student homework assignments that make good use of Info Trac, our free online database of over 4,000 journals. Journals include AIDS Weekly, Archives of Sexual Behavior, Sexuality and Culture, Sex Roles, Gender Issues, and many more. Assignments include class debates that teachers can assign. Includes a "quick start" to Info Trac that explains how to get started using the database